The Reproduction of Inequalities in the Intergenerational Social Mobility Trajectories of Moroccan Youngsters in Spain - Laíz Moreira, Sofía (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
This paper presents the main results of a research carried out between 2011 and 2015 which objective was to analyze the intergenerational social mobility strategies of Moroccan families related to young migrants of three main profiles: second generation migrants, reunifies children and and those arrived as unaccompanied minors. All of them settled in the Autonomous Community of Galicia, in Spain, at the beginning of this century. A mainly ethnographical methodology using a multisided approach has guided a large field work with ten family groups, which members were settled between Galicia and the Province of Beni Mellal, in Morocco. The measurements in educational and professional categories have taken into account the generation of the parents and that of that of children, that’s to say, from an intergenerational point of view. Results have shown upward educational mobility between generations but poor results in regard to offspring’s professional insertion, as they reproduced precarious and weak work conditions as their parents, employed mainly in the informal economy.